Role of Interactive infographics in the Interior design of contemporary museums - Mai Abdel Malik (Journal of Architecture, Art & Humanistic Science, 2018)
This research is an interdisciplinary study exploring the role of infographics and interactive displays in the interior design of museums, showing the impact of new technologies on the process of delivering information and exploring newfangled ways to deliver the interactive experience in developing and promoting new learning techniques. With an intensive focus on the different types of infographics and interactive displays through the exposure to diverse applications and models supporting the creative design ideas, considering it a space for engagement, discovery, learning and playing. Finally, the study emphasized the importance of linking the various disciplines in the design process leading to a successful and integrated design to contribute in sharing knowledge across the world.